Healthcare Waste Management Practices and Its Associated Factors Among Healthcare Workers in Health Facilities in Ethiopia: A Systematic Review and Meta-analysis - Yibeltal Assefa Atalay; Kelemu Abebe Gelaw (SAGE Publishing, 2024)
Introduction: Waste Management Practices have garnered growing interest in hospitals, research facilities, and laboratories over the past few years. However, there seems to be noticeable absence of a comprehensive understanding regarding research on waste management practices in health facilities among healthcare workers. Objective: This study aimed to determine the prevalence and factors associated with healthcare waste management practices among healthcare workers in Ethiopia. Methods: The search was performed by using the Web of Science (WoS) database, PubMed, and the Cochrane Library. To assess the presence of publication bias, by using funnel plots, contour-enhanced funnel plots, trim and fill analysis, and Begg and Egger regression test. A significance level of P ⩽ .05 was used to indicate potential publication bias. Heterogeneity between studies was assessed using the I2 statistics. Results: From retrieved original studies, 15 studies were included in the meta-analysis with a total of n = 5260 healthcare workers. The pooled prevalence of waste management practices in Ethiopia was 52.86% (95% CI = 51.57, 54.15), with significant heterogeneity observed between studies ( I 2  = 97.0%; P  ⩽ .001). Sub-group analysis based on regional distribution in Ethiopia revealed that the highest prevalence of waste management practices was observed in Southern Nation and Nationalities and People's Region with 61.9% (95% CI = 52.953, 64.449). Conclusions: This systematic review and meta-analysis revealed that the pooled prevalence of waste management practices among healthcare workers in Ethiopia was notably low. Training and the presence of guidelines were significantly associated with waste management practices. The healthcare facilities have improved access to and availability of policies related to waste management and the Ministry of Health promotes their use through various means, including training for healthcare professionals.